Pengaruh Product, Promotion, Price dan Place Politik Partai Baru terhadap Preferensi Politik Generasi Milenial pada Pemilihan Legislatif Tahun 2019 - Panjaitan, Mazmur JO; Maryanah, Tabah; Indrajat, Himawan (Journal of Government and Social Issues (JGSI), 2021)
The percentage of PSI in the Legislative Election of Bandar Lampung City obtained 1.31% of the votes in the midst of the millennial generation dominating the election votes, referring to BPS data that the total millennial population got the highest order reaching 449,310 people, so the purpose of this study was to determine the failure of PSI in the Legislative Election through the marketing mix. PSI politics by Firmanzah against millennial political preferences. The research method used a mix method design sequential explanatory. The results of this study show that the four variables marketing mix political, PSI have not implemented the political marketing mix by Firmanzah, include only products that affect the preferences of the millennial generation, because PSI products are still in line with millennials to build and bring change with an anti-corruption and intolerance platform. Variables promotion, price and place have no effect on political preferences, PSI still does not use social media as a campaign promotion tool efficiently, while price PSI does not have a central figure who can influence the preferences of party segments and PSI visits do not touch all levels of society. Meanwhile, the qualitative results indicate that PSI failure occurs due to internal and external factors.